2002
DOI: 10.1038/sj.bjc.6600276
|View full text |Cite
|
Sign up to set email alerts
|

The United Kingdom Childhood Cancer Study of exposure to domestic sources of ionising radiation: 1: radon gas

Abstract: This paper reports the results of the United Kingdom Childhood Cancer Study relating to risks associated with radon concentrations in participants homes at the time of diagnosis of cancer and for at least 6 months before. Results are given for 2226 case and 3773 control homes. No evidence to support an association between higher radon concentrations and risk of any of the childhood cancers was found. Indeed, evidence of decreasing cancer risks with increasing radon concentrations was observed. Adjustment for d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(37 citation statements)
references
References 15 publications
1
35
1
Order By: Relevance
“…Exposure assessment was based on a comprehensive prediction model that was developed and validated using > 40,000 measurements taken throughout Switzerland between 1994 and 2004. Previous case–control studies have reported participation < 55%, and exposure measurements were often limited to subsets of study participants (Cartwright et al 2002; Kaletsch et al 1999; Lubin et al 1998; Maged et al 2000; Steinbuch et al 1999; Stjernfeldt et al 1987). In contrast with ecological studies, we had information on a number of potential individual-level confounders (Laurier et al 2001; Tong et al 2012), although adjusting for these variables did not materially affect hazard ratios, suggesting little or no confounding by these factors although we cannot completely exclude residual confounding due to misclassification in the confounder variables.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Exposure assessment was based on a comprehensive prediction model that was developed and validated using > 40,000 measurements taken throughout Switzerland between 1994 and 2004. Previous case–control studies have reported participation < 55%, and exposure measurements were often limited to subsets of study participants (Cartwright et al 2002; Kaletsch et al 1999; Lubin et al 1998; Maged et al 2000; Steinbuch et al 1999; Stjernfeldt et al 1987). In contrast with ecological studies, we had information on a number of potential individual-level confounders (Laurier et al 2001; Tong et al 2012), although adjusting for these variables did not materially affect hazard ratios, suggesting little or no confounding by these factors although we cannot completely exclude residual confounding due to misclassification in the confounder variables.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between radon exposure and childhood leukemia has been addressed in various case–control studies (Cartwright et al 2002; Kaletsch et al 1999; Kendall et al 2013; Lubin et al 1998; Maged et al 2000; Raaschou-Nielsen et al 2008; Steinbuch et al 1999; Stjernfeldt et al 1987) and ecological studies (Alexander et al 1990; Butland et al 1990; Collman et al 1991; Evrard et al 2005, 2006; Foreman et al 1994; Gilman and Knox 1998; Henshaw et al 1990; Lucie 1990; Muirhead et al 1991; Richardson et al 1995; Thorne et al 1996a, 1996b). Most of the ecological studies reported an association between childhood leukemia and estimated domestic radon exposure.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The United Kingdom Childhood Cancer Study (UKCCS), which included radiation measurements on about 2200 cases of childhood cancer of all types (of which about a third are leukemia) and around twice as many controls (9;10) has, by the results of our paper, little power to detect trends with dose – our calculations suggest that it would require at least 9600 leukemia cases to have 80% power of detecting a positive trend at the 1-sided 5% level.…”
Section: Discussionmentioning
confidence: 99%